Miscellaneous Properties of Generalized Fubini Polynomials - Muhammet Ağca; Nejla Özmen (Communications in Advanced Mathematical Sciences, 2023)
This article attempts to present the generalized Fubini polynomials $F_{n}(x,y,z,q)$. The results obtained here include various families of multilinear and multilateral generating functions, various properties, as well as some special cases for these generalized Fubini polynomials $F_{n}(x,y,z,q)$. Finally, we get several interesting results of this generalized Fubini polynomials and obtain an integral representation.